Rare Pleurotus species with veiled basidiomata from the Neotropics: neotypification of Pleurotus magnificus and epityfication of Pleurotus rickii - Bittencourt, Felipe; Drewinski, Mariana De Paula; Menolli Jr., Nelson; Drechsler-Santos, Elisandro Ricardo (Phytotaxa, 2024)
Knowledge of Pleurotus in Brazil dates back to the 19th century, when European mycologists studied and described numerous Neotropical taxa. Some of these long-described species remain poorly known, mostly due to the lack of recent records, detailed morphological descriptions, and molecular data. During field surveys in Southeast and Southern Brazil, specimens of two rare Pleurotus species with veiled basidiomata, i.e. P. magnificus and P. rickii, were collected. These species are recorded for the first time in the state of Santa Catarina, Brazil, and P. magnificus for the first time in the states of Minas Gerais, Paraná and São Paulo. Updated and detailed morphological descriptions are provided. DNA sequences of the ITS and nLSU molecular markers were obtained for both species, and phylogenetic analyses were conducted to explore their relationships within Pleurotus. A neotype is designated for P. magnificus, and a lectotype and epitype are designated for P. rickii.